A Frame Element Model for the Nonlinear Analysis of FRP-Strengthened Masonry Panels Subjected to In-Plane Loads - Ernesto Grande; Maura Imbimbo; Alessandro Rasulo; Elio Sacco (Advances in Materials Science and Engineering)
A frame element model for evaluating the nonlinear response of unstrengthened and FRP-strengthened masonry panels subjected to in-plane vertical and lateral loads is presented. The proposed model, based on some assumptions concerning the constitutive behaviour of masonry and FRP material, considers the panel discretized in frame elements with geometrical and mechanical properties derived on the basis of the different states characterizing the sectional behaviour. The reliability of the proposed model is assessed by considering some experimental cases deduced from the literature.